Tocilizumab Controls Paraneoplastic Inflammatory Syndrome but Does Not Suppress Tumor Growth of Angiomatoid Fibrous Histiocytoma - Hideaki Sabe; Akitomo Inoue; Shigenori Nagata; Yoshinori Imura; Toru Wakamatsu; Satoshi Takenaka; Hironari Tamiya (Case Reports in Oncological Medicine)
Angiomatoid fibrous histiocytoma (AFH) is a rare soft tissue tumor that rarely metastasizes but lacks effective systemic therapy once it propagates. In some reports, high interleukin-6 (IL-6) production promotes tumor growth by autocrine stimulation and tocilizumab, an IL-6 receptor antagonist, can control AFH growth. Here, we present a case report on a patient with local recurrence and distant lymph node metastasis of AFH treated with tocilizumab. As a result, the inhibition of the IL-6 signaling pathway controlled paraneoplastic inflammatory syndrome (PIS); however, the local recurrent tumor progressed. This case implied that IL-6 is not necessarily the cause of tumor growth in AFH. Therefore, physicians should bear in mind that watchful observation is needed whether tocilizumab can control tumor progression despite the amelioration of PIS associated with the attenuated effect of IL-6 on AFH.